Subnational Insolvency : Cross-Country Experiences and Lessons - Liu, Lili (2012)
Subnational insolvency is a reoccurring event in development, as demonstrated by historical and modern episodes of subnational defaults in both developed and developing countries. Insolvency procedures become more important as countries decentralize expenditure, taxation, and borrowing, and broaden subnational credit markets. As the first cross-country survey of procedures to resolve subnational financial distress, this paper has particular relevance for decentralizing countries. The authors explain central features and variations of subnational insolvency mechanisms across countries. They identify judicial, administrative, and hybrid procedures, and show how entry point and political factors drive their design. Like private insolvency law, subnational insolvency procedures predictably allocate default risk, while providing breathing space for orderly debt restructuring and fiscal adjustment. Policymakers' desire to mitigate the tension between creditor rights and the need to maintain essential public services, to strengthen ex ante fiscal rules, and to harden subnational budget constraints are motivations specific to the public sector.